Upgrading vacuum residue by swelling of CO2 gas and catalytic cracking process by using Al2O3 catalyst. - Aditya Retno Utami; Deby Ansyory; Sri Haryati; Muhammad Djoni Bustan (Program Pascasarjana Universitas Sriwijaya, 2020)
Vacuum residue is a waste of the production process in the petroleum refining industry. Even though vacuum residue is waste, it still contains hydrocarbon compounds that can be reused as a petroleum derivatives products that have commercial value. Improving the quality of vacuum residue from waste to commercial products is carried out in several stage of the process. In this research, we applied the swelling process as an initial step to weaken and break the long chain carbon of vacuum residue in order to reduce energy consumption. Furthermore, the swelling products will be reprocessed in the catalytic cracking processes to improve the quality and quantity of the product yield. The application of the swelling process can reduce operating conditions temperatures up to 350ºC, and the use of Al2O3 catalyst in the cracking process can produces the product yield that have a good quality after performing the GC-MS analysis test. The content of hydrocarbons in this vacuum residue shows the dominance of aromatic compounds with high octane numbers. The optimum composition of 5%-wt catalyst showed chromatogram composition of 166 compounds with the highest peak at 3.26 retention time owned by toluene with an octane number of 91.